Pastoral care : an essential guide - Patton, John, 1930- (Nashville : Abingdon Press, 2005)
Publisher's description: The purpose of the Abingdon Essential Guides is to fulfill the need for brief, substantive, yet highly accessible introductions to the core disciplines in biblical, theological, and religious studies. Drawing on the best in current scholarship, written with the need of students foremost in mind, addressed to learners in a number of contexts, Essential Guides will be the first choice of those who wish to acquaint themselves or their students with the broad scope of issues, perspectives, and subject matters within biblical and religious studies....[discusses] four major kinds of lostness: grief, illness, abuse, and family challenges.
1. Pastoral wisdom -- 2. Pastoral presence -- 3. Pastoral guidance -- 4. Limit, loss, and grief -- 5. Care for the sick -- 6. Abuse of self and others -- 7. Care of marriage and family -- 8. Pastoral counseling -- A final reflection.
Includes bibliographical references (p. 119-122)
Keywords: Pastoral counseling; Family counseling; Grief therapy; Abuse